Service Loyalty the Effects of Service Quality and the Mediating Role of Customer Satisfaction "A Case Study: PT. Sabda Alam Hotel" - Budiarta, Sandy Indimas; Fachira, Ira (Journal of Business and Management, 2017)
Abstract The following study has purpose to find the relationship between service quality dimensions towards Customer Satisfaction as mediating role and Customer Loyalty in PT Sabda Alam Hotel. This research came from a problem which was appeared from the company which show the number of customer decrease annually. Path analysis was conducted to investigate Customer Satisfaction as a mediational model that links service quality to Customer Loyalty.  Appropriate measures are identified from 177 Sabda Alam customer from 2010 – 2015 as the population. The result indicate that Customer Satisfaction does not play a mediating role in the effect of independent and dependent variable. However, the result shows that there is an impact on service quality to Customer Loyalty directly. A recommendation that the company should do is to improve their service quality in every aspects to increase the level of Customer Satisfaction and Customer Loyalty. Keywords:  Service quality, Customer Satisfaction, Customer Loyalty, Hospitality, SERVQUAL